2001
DOI: 10.1159/000056077
|View full text |Cite
|
Sign up to set email alerts
|

No Effect of Phenobarbital Pretreatment of Rats on Methotrexate Pharmacokinetics in the Isolated Liver Perfused in a Single-Pass Way

Abstract: Pretreatment of the rat with phenobarbital (PB) is known to increase gene expression of the canalicular multispecific organic anion transporter (cMOAT) and hepatobiliary transport of its substrates (glutathione, sulfobromophthalein). To determine the effect of PB on the hepatobiliary transport of methotrexate (MTX, another substrate of cMOAT) and its metabolism to 7-hydroxymethotrexate (7-OHMTX) in the rat, we compared the steady-state pharmacokinetics of MTX in the isolated liver of either PB-pretreated (80 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
2
2
0
Order By: Relevance
“…1 and Figs. 2 and 4) are in agreement with previous reports16, 34, 42, 43 on the hepatobiliary disposition of MTX in different IPRL models. In one of the earlier studies, Strum and Liem34 demonstrated that the hepatic uptake of MTX in a recirculating IPRL is a saturable process with a maximum velocity ( V max ) of 11.1 µmol/h/g and a Michaelis–Menten constant ( K m ) of 1.3 mM.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…1 and Figs. 2 and 4) are in agreement with previous reports16, 34, 42, 43 on the hepatobiliary disposition of MTX in different IPRL models. In one of the earlier studies, Strum and Liem34 demonstrated that the hepatic uptake of MTX in a recirculating IPRL is a saturable process with a maximum velocity ( V max ) of 11.1 µmol/h/g and a Michaelis–Menten constant ( K m ) of 1.3 mM.…”
Section: Discussionsupporting
confidence: 92%
“…A similar observation was also made by Strum and Liem34 who showed that the biliary excretion rate of MTX paralleled its hepatic uptake rate at low perfusate concentrations of MTX. Furthermore, an unexpected lack of effect of Mrp2 induction by phenobarbital on the biliary excretion rate of MTX in a recirculating IPRL model with an initial MTX concentration similar to ours was attributed to a rate‐limiting hepatic sinusoidal uptake 43. Collectively, these studies indicate that at or below the concentrations used in our studies, the hepatic uptake is the rate‐limiting step in the biliary excretion of MTX.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…MTX, a commonly used antimetabolite drug in cancer treatment, is known to have toxic effects through the dysregulation of oxidative stress that occurs during its metabolism in the liver. [ 13 ] These oxidative reactions can cause hepatotoxicity, which consists of hepatic steatosis, cholestasis, fibrosis, and cirrhosis. [ 14 ] In addition, several studies have shown that the interaction of oxidants and antioxidants is linked with the development of several pathological processes associated with chemotherapy‐induced organ injury, particularly in the liver and kidney.…”
Section: Discussionmentioning
confidence: 99%